BIOCHEMICAL PROPERTIES OF MAIZE PLANT AND METHODS OF ITS DETERMINATION - Boltayeva M. D.; Yuldashov O. X. (Bright Mind Publishing, 2025)
The article examines the main biochemical composition of maize and the methods for its determination. Information is provided on spectrophotometry, chromatography, and chemical analysis methods for determining carbohydrate, protein, fat, and vitamin content. These analyses are essential for assessing the nutritional value and quality control of maize.
Keywords: Maize, grain, fat, carbohydrate, amylose, Kjeldahl method, spectrophotometry, gas chromatography, chlorophyll content, vitamin.